2012
DOI: 10.1363/4403912
|View full text |Cite
|
Sign up to set email alerts
|

Designing Messages to Motivate Parents To Get Their Preteenage Sons Vaccinated Against Human Papillomavirus

Abstract: CONTEXT Human papillomavirus (HPV) vaccine, licensed for use in 9–26-year-olds, is most effective when given before sexual activity begins. HPV causes genital warts, is associated with several cancers and disproportionately affects racial and ethnic minorities. Parents are typically unaware of male HPV vaccine; messages that might motivate them to get their preteenage sons vaccinated are unexplored. METHODS Messages promoting vaccination of preteenage boys were designed and tested in 2009 and 2010. Five focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…1113,22 For example, in a statewide sample of Minnesotan vaccine providers, we found that half of respondents reported that parents request to delay HPV vaccination for younger adolescents “often” or “most of the time.” 13 Interestingly, these perceptions of strong parental hesitancy are generally at odds with research among parents themselves, which finds that a majority value HPV vaccine, are willing to vaccinate, and would prefer to receive strong recommendations from their children’s providers. 4,11,14,2324 Most of the physicians in our study reported that not having school entry requirements for HPV vaccine contributed to parental hesitancy, and this finding may offer one clue as to why physicians perceive communication about HPV vaccine to be burdensome. Without the supportive policy environments which surround Tdap and, to a lesser extent, meningococcal vaccination, 25 physicians are left to make a case for HPV vaccination without recourse to the law.…”
Section: Discussionmentioning
confidence: 66%
“…1113,22 For example, in a statewide sample of Minnesotan vaccine providers, we found that half of respondents reported that parents request to delay HPV vaccination for younger adolescents “often” or “most of the time.” 13 Interestingly, these perceptions of strong parental hesitancy are generally at odds with research among parents themselves, which finds that a majority value HPV vaccine, are willing to vaccinate, and would prefer to receive strong recommendations from their children’s providers. 4,11,14,2324 Most of the physicians in our study reported that not having school entry requirements for HPV vaccine contributed to parental hesitancy, and this finding may offer one clue as to why physicians perceive communication about HPV vaccine to be burdensome. Without the supportive policy environments which surround Tdap and, to a lesser extent, meningococcal vaccination, 25 physicians are left to make a case for HPV vaccination without recourse to the law.…”
Section: Discussionmentioning
confidence: 66%
“…There may be a role for testing state and federally designed social marketing campaigns beyond approaches taken in the past, 29 which have been limited in scope. 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Given that HPV-infected boys are not only subject to HPV-associated cancers but increased risk of HPV-related diseases for their sexual partners, 21,22 health care providers and public health officials should strive to inform parents of male children about the HPV vaccines, which may directly lead to increased uptake. 23 Furthermore, as older children are more likely to be sexually active, it is essential that they be vaccinated before their first sexual experience. Therefore, from a life course perspective, it is imperative that HPV awareness is promoted among parents of younger children to ensure vaccination at age 11 to 12 years, which can prevent subsequent HPV-related disease burden.…”
Section: Discussionmentioning
confidence: 99%